2003
DOI: 10.1039/b211185c
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of the initial reaction between OH and isoprene in tropospheric conditions

Abstract: The reaction of isoprene with OH radicals has been investigated by ab initio molecular orbital theory. We report the energetics of four different pathways, involving the direct addition of OH to four of the carbon atoms. Calculations have been performed using both density functional theory (BHandHLYP) and Møller-Plesset perturbation theory to the second-order (MP2). Two pre-reactive complexes have been identified, whose stabilization energy with respect to the separated reactants is about 12 kJ mol À1 . Their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
53
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 31 publications
7
53
1
2
Order By: Relevance
“…Francisco-Márquez and coworkers predicted four pre-reactive complexes for isoprene, two for each isoprene conformation, using BHandHLYP and MP2 theories with the 6-311G** basis set 39,56. Their pre-reactive complexes, when isoprene is in the s-trans conformation, have a E zpv of −2.80 and −2.99 kcal·mol −1 (BHandHLYP) and −3.30 and −3.49 kcal·mol −1 (MP2) relative to the reactants, and lie below the transition state.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Francisco-Márquez and coworkers predicted four pre-reactive complexes for isoprene, two for each isoprene conformation, using BHandHLYP and MP2 theories with the 6-311G** basis set 39,56. Their pre-reactive complexes, when isoprene is in the s-trans conformation, have a E zpv of −2.80 and −2.99 kcal·mol −1 (BHandHLYP) and −3.30 and −3.49 kcal·mol −1 (MP2) relative to the reactants, and lie below the transition state.…”
Section: Discussionmentioning
confidence: 99%
“…Adduct formation is favored along the four C 1 and C 4 pathways, by a minimum of 6.1 kcal·mol −1 with respect to the C 2 and C 3 pathways. This is consistent with twenty previous calculations whose ΔH 298 ° and ΔE reaction energies for pathway C 1 180 range from −31.5 to −47.7 kcal·mol −1 (average = −39.6), for C 2 180 range from −13.4 to −32.1 (average = −26.2), for C 3 180 range from −14.6 to −31.7 (average = −25.6), and for C 4 180 range from −29.6 to −45.0 kcal·mol −1 (average = −37.1) 24,25,39,51,56. In regards to isoprene’s s-gauche conformation, Francisco-Marquez and coworkers determined PMP2/cc-pVTZ//MP2/6-311G** and BHandHLYP/6-311G(d,p)//BHandHLYP/6-311G(d,p) reaction energies along the C 1 41:C 2 41:C 3 41:C 4 41 pathways, with values of −44.7:−27.3:−26.6:−42.8 and −38.0:−21.0:−20.7:−36.1 kcal·mol −1 , respectively 56.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The energies of AC1 and AC4 are about 5–18 kcal/mol lower than the energies of AC2 and AC3. This is due to the fact that AC1 and AC4 are stabilized by allylic resonance, while AC2 and AC3 are not (Figure ) …”
Section: Resultsmentioning
confidence: 99%
“…This is due to the fact that AC1 and AC4 are stabilized by allylic resonance, while AC2 and AC3 are not ( Figure 7). 4,5,11,13,31,36,37,40 Isomers AC2R and AC3R are produced by isomerization of the vibrationally excited hydroxyacyl radicals AC2 and AC3. It was found that the rearrangement after addition is observed at sites C2 and C3, but not at sites C1 and C4, probably because hydroxyacyl radicals AC1 and AC4 are more stable than AC2 and AC3.…”
Section: Resultsmentioning
confidence: 99%